60.5k views
20 votes
93 + 12m = 3(4m – 1) + 96

User Mchangun
by
5.3k points

2 Answers

7 votes

Answer:

infinite solutions

Explanation:

First, you do the property of distribution

93+12m=3(4m-1) +96

93+12m=12m-3+96

then you combine like terms

93+12m=12m+93

0=0 is the answer if you were to continue.

User Nona
by
5.5k points
5 votes

Answer:

m=0

Explanation:

We simplify the equation to the form, which is simple to understand

93+12m=3(4m-1)+96

Reorder the terms in parentheses

93+12m=+(+12m-3)+96

Remove unnecessary parentheses

+93+12m=+12m-3+96

We move all terms containing m to the left and all other terms to the right.

+12m-12m=-3+96-93

We simplify left and right side of the equation.

m=0

Hope this helps!

Brain-List?

User Alawatthe
by
5.6k points